Determination of the apparent and true ileal amino acid digestibility and digestible and metabolizable energy of specialty protein sources intended for nursery pig diets - Gottlob, R.O.; Hastad, C.W.; Lawrence, K.R.; Knabe, D.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to determine the apparent and true-ileal amino acid digestibility, and to determine the digestible energy and metabolizable energy values of rice protein concentrate, salmon protein hydrolysate, whey protein concentrate, and spray-dried animal plasma. The experimental ingredients were analyzed for essential and non-essential amino acids and crude protein so diets could be formulated. In Exp.1, pigs were fed each diet, and ileal digesta was collected and analyzed. Apparent and true digestibilities were then calculated. In Exp. 2, pigs were fed each diet and feces were collected, weighed, and sampled. Lab analyses were conducted for the determination of gross energy (GE) and digestible energy (DE). Then ME values were determined by calculation from the DE and CP concentrations of experimental diets. In Exp. 1, TID lysine, methionine, and threonine values were 86.6, 69.0, and 78.9% for rice protein concentrate; 89.7, 88.7, and 80.2% for salmon protein hydrolysate; 95.7, 93.9, and 88.4% for whey protein concentrate; and 95.4, 93.5, and 92.2% for spray-dried animal plasma, respectively. In Exp. 2, DE values for rice protein concentrate, salmon protein hydrolysate, whey protein concentrate, and spray-dried animal plasma were 2143, 1893, 2245, and 2062 kcal/lb, respectively. The ME values that were determined for the protein products were 1917, 1598, 1974, and 1805 kcal/lb, respectively.
Keywords: Swine; Digestibility; Pigs; Rice protein concentrate; Salmon protein hydrolysate; Whey protein concentrate; Spray-dried animal plasma